Determination of Total Flavonoid Levels of Bajakah Wood Extract (Spatholobus Littoralis Hassk) on Various Ethanol Concentrations and Antibacterial Activity Test of Staphylococcus Aureus - Siti Rahmasari; Ridwanto Ridwanto; Anny sartika daulay; Haris Munandar Nst (Eduvest - Journal of Universal Studies, 2025)
The bajakah plant is one of the biological plants used in traditional medicine. Bajakah is also a medicinal herbal plant that can be used in all its parts. This plant can be found in the depths of Kalimantan Province, but it has not spread to other regions. There has been no effort to cultivate bajakah because of the lack of understanding of the local population about the use of this plant. This research includes the stages of processing plant materials, making ethanol extracts, characterization examinations, phytochemical screening, and determining total flavonoid levels of ethanol extract of Bajakah wood using the visible spectrophotometry method and antibacterial activity. Bajakah wood extract was made by maceration method using ethanol concentrations of 96%, 70%, and 50%, and the extract obtained was concentrated with a rotary evaporator, then the total flavonoid level was determined using the visible spectrophotometry method and antibacterial activity tests were carried out against Staphylococcus aureus As a positive control using chloramphenicol and negative control using dimethyl sulfoxide. The results were obtained by determining the maximum wavelength of quercetin and operating time, measuring the quercetin calibration curve, and calculating the total flavonoid level using the visible spectrophotometry method. The results obtained in the determination of total flavonoid levels in Bajakah wood ethanol extract at a concentration of 96% were 349.888 ± 4.5022 mg QE/g, at a 70% concentration of 307.137 ± 6.7626 mg QE/g and a 50% concentration of 6.15173 ± 2.9148 mg QE/g.